Descripción y evaluación de una técnica de ovariohisterectomía laparoscópica en perras sanas - Ruíz S., Isabel; Acevedo, Carlos M.; Rodríguez, Marta (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary An ovary-hysterectomy (OH) laparoscopic procedure was performed in 20 healthy female dogs of several ages. The surgical protocol is described, taking into account the instruments used, patient preparation, surgery area preparation, surgical position of the patient, points localization, and stages of the surgical technique using a laparoscopic procedure. Complications inherent to the technique were also analyzed. The patients recovered of anesthesia without any complications. The OH through laparoscopy can be done safety and with minimum periods of recuperation and trans- and post-surgical complications.